Hippo‐YAP signaling pathway: A new paradigm for cancer therapy. Issue 10 (22nd July 2014) - Ma, Yanlei; Yang, Yongzhi; Wang, Feng; Wei, Qing; Qin, Huanlong
<x xml:space="preserve">Abstract</x> In the past decades, the Hippo signaling pathway has been delineated and shown to play multiple roles in the control of organ size in both Drosophila and mammals. In mammals, the Hippo pathway is a kinase cascade leading from Mst1/2 to YAP and its paralog TAZ. Several studies have demonstrated that YAP/TAZ is a candidate oncogene and that other members of the Hippo pathway are tumor suppressive genes. The dysregulation of the Hippo pathway has been observed in a variety of cancers. This review chronicles the recent progress in elucidating the function of Hippo signaling in tumorigenesis and provide a rich source of potential targets for cancer therapy.